Tecendo nossos caminhos - Kanunxi, Cledson; Xinunxi, Jackson; Tipuici, Marta; Utopic Documentaries (Firm) ([Brazil] : Povo Manoki, 2019)
Only six elders of the Manoki population in the Brazilian Amazon still speak the indigenous language, an imminent risk of losing this important dimension of their modes of existence. Decided to resume their language with the older ones, the younger ones decide to narrate their challenges and desires in images and words. From the analogy with the fragility of cotton that turns into a strong thread to support the heavy net, Marta Tipuici talks about the resistance of her people, her relationship with her grandmother and the hope of speaking her language again in the new generations.--
Narrator: Marta Tipuici
In Portuguese and Manoki; closed captioning available in English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 28, 2021)
Keywords: Iranxe Indians -- Brazil; Iranxe language; Indigenous peoples -- Brazil; Documentary films; Nonfiction films; Internet videos; Short films; Streaming video